IMPLEMENTATION OF FERTILIZER SUBSIDIES: IMPACT ON AGRICULTURE AND FOOD SECURITY IN INDONESIA (A CRITICAL REVIEW) - Mega Amelia Putri; Werry Darta Taifur; Nasri Bachtiar (Transpublika Publisher, 2023)
Fertilizer subsidies are an essential economic policy affecting Indonesia's agricultural sector and food security. This article critically reviews the implementation of fertilizer subsidies and its impact on agricultural economic growth. We analyze changes in policies and approaches implemented in recent years and their impact on resource allocation efficiency and agricultural productivity. By considering the interactions between government policies, agricultural markets, and economic dynamics, this Research identifies factors that influence the success and failure of fertilizer subsidy programs from an economic perspective. The results provide in-depth insight into the impact of fertilizer subsidy policies on economic growth in the agricultural sector and food security in Indonesia and provide a basis for improving more efficient and sustainable policies.